Left ventricular Dysfunction in Normotensive Diabetic Patients - Ali, Mohammad; Rahman, Md Hafizur; Khokan, Muhammad Kamruzzaman; Rahman, Md Helalur; Rahman, Mohammad Haresur; Islam, Md Belalul (Journal of Comilla Medical College Teachers’ Association, 2024)
Background: Diabetes is a major risk factor for impaired left ventricular function independent of coronary artery disease and hypertension. Left ventricular diastolic dysfunction is demonstrated in diabetic patients who are normotensive and have no symptoms of cardiac disease. Increased mortality is evident among type II diabetic patients with left ventricular failure with preserved ejection fraction also suggests its causative role diastolic dysfunction. Objective: To describe Left ventricular dysfunction in normotensive diabetic patients. Method: A Cross Sectional Study was undertaken in Comilla Medical College Hospital in 51 patients .29 diabetic patients with normal blood pressure (blood pressure ≤140/90 mmHg) who are not on anti-hypertensive medications and 22 healthy controls enrolled into the study. All patients and control subjects underwent transthoracic echocardiographic evaluation using GE LOGIQ V2 machine. The categorical variables described as frequencies and percentages, while continuous variables presented as medians and interquartile range (IQR) values and means and standard deviations. Continuous variables were compared using the Student’s t- test, while categorical parameters were analyzed with the Chi-square test or two tailed Fischer’s exact test as appropriate. A P-value of 0.05 or less was considered statistically significant. Result: Among 51 patients, 29 were cases and 22 were control. Male to female ratio was 1:1.7. The mean ages were 50.03±12.75 and 41.59±11.25 in case and control group respectively. The body mass index in two groups did not showed any significant difference (21.12±4.1 versus 20.91±3.60: P=0.374). The cases had a normal but significantly lower mean ejection fraction than controls (56.98±13.06 versus 62.48±7.73, respectively: P=0.033). Left ventricular diastolic filling pattern was abnormal in 17 (59%) cases and 6 (28%) in control group. The mean relative wall thickness (RWT) was higher in cases than controls. (0.47±0.11 versus .42±0.08; P= 0.014). Also the same difference observed in case of left ventricular mass index. (101.55±35.45 versus 86.98±28.01; P=0.053). The respondents were normotensive but abnormal filling pattern was observed in 17 (59%) and 6 (28%) in cases and control groups respectively which was significant. (P= 0.00018). Conclusion: Normotensive diabetic patients have asymptomatic diastolic dysfunction. J Com Med Col Teachers Asso July 2024; 28(2): 53-57